The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9030715
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Antibodies Binding to Negative Elongation Factor E in Sarcoidosis

Abstract: Sarcoidosis is characterized by multiorgan involvement and granulomatous inflammation. Its origin is unknown and the potential role of autoimmunity has not been sufficiently determined. We investigated the presence of autoantibodies in sarcoidosis using protein array technology. The derivation cohort consisted of patients with sarcoidosis (n = 25) and controls including autoimmune disease and blood donors (n = 246). In addition, we tested a validation cohort including pulmonary sarcoidosis patients (n = 58) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, noteworthy preliminary unpublished data from the same group suggests that NELF-E auto-antibodies may develop because of a mimicry between a certain part of the amino acid sequence of NELF-E and Mycobacteroides abscessus or other bacteria. This noteworthy contribution from Baerlecken et al reinforces the discussion about the classification of sarcoidosis among the vast spectrum of immune or inflammatory systemic diseases, which has always been a puzzle—immune granulomatous disease (association of innate and adaptative immunity; activation and typical granulomas), auto-inflammatory disease (inflammasome activation) or auto-immune disease (humoral and/or immune recognition of autoantigens) [ 16 ]? Or, closer to reality, a polygenic auto-inflammatory disease with autoimmune features [ 9 , 22 ]?…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…However, noteworthy preliminary unpublished data from the same group suggests that NELF-E auto-antibodies may develop because of a mimicry between a certain part of the amino acid sequence of NELF-E and Mycobacteroides abscessus or other bacteria. This noteworthy contribution from Baerlecken et al reinforces the discussion about the classification of sarcoidosis among the vast spectrum of immune or inflammatory systemic diseases, which has always been a puzzle—immune granulomatous disease (association of innate and adaptative immunity; activation and typical granulomas), auto-inflammatory disease (inflammasome activation) or auto-immune disease (humoral and/or immune recognition of autoantigens) [ 16 ]? Or, closer to reality, a polygenic auto-inflammatory disease with autoimmune features [ 9 , 22 ]?…”
mentioning
confidence: 79%
“…This debate has been illustrated by the Mahévas et al study on the association of sarcoidosis and immune thrombocytopenia [ 15 ]. The report of auto-antibodies functional against Negative Elongation Factor E (NELF-E) in sarcoidosis by Baerlecken et al makes an additional significant contribution to the discussion of the “nature” of sarcoidosis [ 16 ]. J Grunewald and his team deserve the credit for demonstrating that auto-immunity, especially towards vimentin as an autoantigen, is a component of sarcoidosis as a disease [ 17 , 18 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with sarcoidosis frequently have higher titers of autoantibodies than healthy individuals [27][28][29]. Several autoantibodies, including anti-mitochondrial, anti-nuclear, anti-double stranded DNA, anti-citrullinated cyclic peptide, rheumatoid factor, antivimentin, and anti-negative elongation factor E, have been detected in sarcoidosis [27][28][29][30][31][32][33][34]. To the best of our knowledge, no previous study has reported anti-gAChR antibodies in sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%